Bargaining for an Assortment - Aydin, Goker; Heese, H. Sebastian (Management Science, 2015)
A retailer’s assortment decision results from a process of give-and-take, during which the retailer may bid manufacturers against one another, and the terms of trade offer plenty of flexibility for allocating the profit among the retailer and manufacturers. We adopt a bargaining framework to capture such an assortment selection process. We investigate the properties of the profit allocations that could emerge in a decentralized supply chain. In our model, the retailer engages in simultaneous bilateral negotiations with all manufacturers. Our model and analysis produce managerial insights that could not be obtained in the absence of a bargaining perspective on assortment planning. For example, we find that when a manufacturer improves its product, such improvements not only benefit the retailer but might even benefit competing manufacturers. In fact, even improvements to out-of-assortment products can increase the profits of the retailer and certain in-assortment manufacturers. Hence, our results suggest that a manufacturer can benefit from collaborating with judiciously chosen competitors. This paper was accepted by Serguei Netessine, operations management.